2008
DOI: 10.1039/b716141g
|View full text |Cite
|
Sign up to set email alerts
|

Chemical modification of crystal-like mesoporous phenylene-silica with amino group

Abstract: Amination of phenylene moieties in crystal-like mesoporous silica hybridized with phenylene is successfully achieved with close to 28% conversion of phenylene by a two-step chemical transformation process while preserving both the ordered mesostructure and crystal-like molecular scale periodicity of the parent material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(102 citation statements)
references
References 17 publications
4
95
0
3
Order By: Relevance
“…After 24 h of stirring at room temperature, followed by 24 h hydrothermal treatment at 100 C, the powder was recovered by filtration, washed with water and dried at 60 C. The template was extracted using an etha noleHCl solution. The incorporation of functional amino groups into the phenylene rings (to obtain NH 2 Bph PMO) was achieved upon two step treatment with very strong acid solutions of HNO 3 eH 2 SO 4 and SnCl 2 eHCl using the same procedure of Ohashi et al [14].…”
Section: Bph Pmo Synthesis and Functionalizationmentioning
confidence: 99%
See 2 more Smart Citations
“…After 24 h of stirring at room temperature, followed by 24 h hydrothermal treatment at 100 C, the powder was recovered by filtration, washed with water and dried at 60 C. The template was extracted using an etha noleHCl solution. The incorporation of functional amino groups into the phenylene rings (to obtain NH 2 Bph PMO) was achieved upon two step treatment with very strong acid solutions of HNO 3 eH 2 SO 4 and SnCl 2 eHCl using the same procedure of Ohashi et al [14].…”
Section: Bph Pmo Synthesis and Functionalizationmentioning
confidence: 99%
“…4) [14,18]. This is an important CeC coupling reaction of a carbonyl group with a compound containing an activated methy lene group (Fig.…”
Section: Catalytic Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…9). 111 It was found that close to 28% of the bridging phenylene in the pore wall was transformed without destroying both the ordered mesoporous structure and pore-wall crystallinity of the parent material. The aminated PMO was an efficient catalyst in a typical base-catalyzed reaction, the Kn€ oevenagel condensation reaction of benzaldehyde and malononitrile.…”
Section: Pmos As Catalysts For Miscellaneous Reactionsmentioning
confidence: 99%
“…Surface modification can be carried out through modifying the organic moieties in bridged hybrid materials. For examples, sulfonation [25], amination [26] and formation of arenetricarbonyl complexes ( C 6 H 4 M(CO) 3 , M = Cr, Mo) [27], have already been successfully achieved on phenylene bridged hybrid materials and applied as catalysts [28]. It should be noted that this kind of surface modification is totally different from the Si O Si R bonding method, which widely adopted in the preparation of stationary phases.…”
Section: Introductionmentioning
confidence: 99%